2020
DOI: 10.1111/1468-2427.12892
|View full text |Cite
|
Sign up to set email alerts
|

A Safer Housing Agenda for Women: Local Urban Planning Knowledge and Women's Grassroots Movements in Medellín, Colombia

Abstract: This essay looks at the process through which women's grassroots movements in Medellín, Colombia, were effective in ensuring that a gender perspective was incorporated into the city masterplan with the aim of making Medellín a safer city for women. Drawing on interviews with activists of the Mesa de Trabajo Mujer de Medellín (MTMM), one of the largest networks among women's grassroots movements, and interviews with officials working at the Office of the Secretary for Women and the Department of Planning, I arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Some general handbooks and guidelines from international organizations and from regional governments and municipalities, reflecting some successful practices and recommendations, were also reviewed. Particularly, the innovative ex- From the review, it was found that gender perspective in urban planning research has typically focused on safety [38][39][40][41], women's participation in urban planning [42][43][44], accessibility [45,46], care services [47], transport [48,49], and housing [50]. Research on site-specific problems has also considered its link to different views (in particular cultural contexts and environments) [39,51] but rarely included criteria of gender views in urban design with a holistic approach aimed at improving conditions in vulnerable areas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some general handbooks and guidelines from international organizations and from regional governments and municipalities, reflecting some successful practices and recommendations, were also reviewed. Particularly, the innovative ex- From the review, it was found that gender perspective in urban planning research has typically focused on safety [38][39][40][41], women's participation in urban planning [42][43][44], accessibility [45,46], care services [47], transport [48,49], and housing [50]. Research on site-specific problems has also considered its link to different views (in particular cultural contexts and environments) [39,51] but rarely included criteria of gender views in urban design with a holistic approach aimed at improving conditions in vulnerable areas.…”
Section: Methodsmentioning
confidence: 99%
“…Particularly, the innovative ex- From the review, it was found that gender perspective in urban planning research has typically focused on safety [38][39][40][41], women's participation in urban planning [42][43][44], accessibility [45,46], care services [47], transport [48,49], and housing [50]. Research on site-specific problems has also considered its link to different views (in particular cultural contexts and environments) [39,51] but rarely included criteria of gender views in urban design with a holistic approach aimed at improving conditions in vulnerable areas. The latter was the basis to propose a model of indicators that include gender views in urban planning in distressed areas.…”
Section: Methodsmentioning
confidence: 99%
“…An influx of studies on the Global South are considering gender within the local planning practice [14][15][16][17]. Lirio [14], for instance, shows how female grassroots groups demanded the inclusion of gender within the planning process in Medellin, Colombia, and acted as designers by providing their local knowledge to build safer houses for them and their families. Gutierrez Rivera illustrates how women's grassroots movements are actors in the planning process with clear ideas of how to ensure a gender perspective in local planning.…”
Section: A Note On Gender Equality and Local Planningmentioning
confidence: 99%
“…During my research the native category casa (house)—rather than vivienda (housing)—emerged with singular strength: both as the place where I carried out the research and as places which acquired relevance in the residents’ search for protection. In addition to class inequalities, there are gender differences linked to the home such as the unequal distribution of domestic work and the changing articulations between the public and private dimensions of men and women, as well as the violence and abuse inflicted on many women and children, usually by their partners or other household members (see Gutiérrez Rivera, this issue, 2020). In fact, gender inequalities seem to be transversal to different neighbourhoods, from gated communities (Atkinson and Smith, 2012) to informal settlements (Meth, 2017).…”
Section: Introductionmentioning
confidence: 99%